1998
DOI: 10.1002/(sici)1099-0496(199810)26:4<250::aid-ppul3>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sputum oscillations and rhDNase in vitro: A combined approach to treat cystic fibrosis lung disease

Abstract: Mucolytic treatment with rhDNase is part of the current therapy for cystic fibrosis (CF) lung disease. The Flutter® valve, a device for enhancing airway mucus clearance, has recently been approved for use in CF patients. Exhalation through the Flutter® valve leads to oscillations of expiratory airflow, improving mucus viscoelasticity and stimulating clearance. The goal of our in vitro study was to evaluate the individual and combined effects of Flutter® valve oscillations and rhDNase treatment on the viscoelas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…This change of log 0.5 represents a 3-fold increase of viscoelasticity on a linear scale. Furthermore, log G* Fig 2: A) viscoelasticity at 10 radian/s on a logarithmic scale (log G*; d y n / c m 2 ), B) mucociliary clearability index (MCI) and C) cough clearability index (CCI) of mucus samples in RAO-affected (principal g roup) and control horses (control group) before (0) and after e n v i ronmental challenge (6, 24 and 48 h) values of 3 and more are in the range found in human patients suffering from severe airway obstruction caused by cystic fibrosis (Dasgupta et al 1998). The ratio of viscosity/elasticity did not differ between controls and RAO-horses and was not affected significantly by stabling and hay challenge.…”
Section: Discussionmentioning
confidence: 90%
“…This change of log 0.5 represents a 3-fold increase of viscoelasticity on a linear scale. Furthermore, log G* Fig 2: A) viscoelasticity at 10 radian/s on a logarithmic scale (log G*; d y n / c m 2 ), B) mucociliary clearability index (MCI) and C) cough clearability index (CCI) of mucus samples in RAO-affected (principal g roup) and control horses (control group) before (0) and after e n v i ronmental challenge (6, 24 and 48 h) values of 3 and more are in the range found in human patients suffering from severe airway obstruction caused by cystic fibrosis (Dasgupta et al 1998). The ratio of viscosity/elasticity did not differ between controls and RAO-horses and was not affected significantly by stabling and hay challenge.…”
Section: Discussionmentioning
confidence: 90%
“…After 30 min of flutter oscillation, studies have reported a decrease in the rigidity factor of mucus samples and mucus viscosity, but no change in mucociliary transport and cough. 19 21 However, after 4 weeks of treatment with flutter there was an increase in the mucociliary and cough clearance indices and an increase in the in vitro mucus cough transport. 22 , 23 A Cochrane review concluded that there is no clear evidence whether oscillation was a more or less effective intervention overall than other forms of physiotherapy in cystic fibrosis patients.…”
Section: Discussionmentioning
confidence: 97%
“…Various mechanisms of action have been proposed for HFCWO: (1) augmentation of the expiratory flow, which increases the annular flow of mucus towards the oropharynx when exceeding by more than 10% the inspiratory peak flow [ 16 18 ]; (2) improvement of mucus rheological (spinnability and viscoelastic) properties [ 19 , 20 ]; (3) increase of ciliary motility by reflected stimulation of vagus nerve, in particular when the applied oscillations range between 11 and 15 Hz [ 21 ]; and (4) enhancement of the gas-liquid transport [ 16 , 22 ]. Recent findings showed that HFCWO, when compared to conventional physiotherapy, improves the amount of aerated lung regions and oxygenation of intubated patients in intensive care unit (ICU) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%